ANALISIS OPINI PUBLIK MENGENAI BATAS USIA PENGGUNAAN SOSMED ANAK INDONESIA MENGGUNAKAN PENDEKATAN MACHINE LEARNING - Prima Lydia; Muhammad Irfan Sarif; Nauval Alfarizi; Sri Hidayati; Adi Putra (Smart Education, 2026)
Abstract: This research looks at how people feel about government rules that limit children under 16 from using social media. This study uses data consisting of 4,651 social media posts obtained through scraping, as well as questionnaire responses from 338 participants at a public junior high school in the Deli Serdang region.In this study, two types of classification models were used: Support Vector Machine (SVM) and Random Forest. These models were compared to see how well they perform. This method serves as a means of achieving relatively similar levels of accuracy. The results indicate that both models perform at comparable accuracy levels. However, SVM demonstrates superior performance in maintaining class balance, as indicated by a higher macro F1-score of 0.85, compared to Random Forest, which tends to be more biased toward the neutral class. Further analysis shows that the neutral class is the most common in the sentiment distribution. Additionally, the models often have difficulty accurately recognizing positive sentiment, probably because they tend to be cautious and classify uncertain inputs as neutral. This study doesn't use special methods to balance the data, so it can check how well the model works when the data is naturally unbalanced. This method helps us understand how public opinion reacts to government policies, especially those affecting children, as the main focus of the analysis. Keywords: Access Restriction, Sentiment Analysis, Public Opinion, Children, Social Media Abstrak: Penelitian ini bertujuan menganalisis perasaan masyarakat umum terhadap kebijakan yang dibuat pemerintah yang membatasi akses anak di bawah usia 16 tahun ke media sosial. Data yang digunakan berasal dari hasil pengumpulan data melalui scraping media sosial sebanyak 4651 data dan data dari kuesioner yang diisi oleh 338 responden dari salah satu SMP Negeri Wilayah Deli Serdang. Model klasifikasi yang digunakan dalam penelitian ini adalah Support Vector Machine (SVM) dan Random Forest sebagai perbandingan dalam melihat performa. Hasil pengujian menunjukkan kedua model memiliki tingkat akurasi relativ sama. Namun, SVM menunjukkan hasil yang lebih baik dalam menjaga keseimbangan antar kelas dengan skor F1 makro sebesar 0,85, dibandingkan dengan Random Forest yang cenderung lebih condong ke kelas netral. Analisis lebih lanjut menunjukkan bahwa kelas netral mendominasi dalam penyebaran sentimen, Kemudian, model juga sering kesulitan dalam mengenali perasaan positif dikarenakan model cenderung konservatif dengan memilih netral. Dalam penelitian ini tidak mengklasifikasi secara khusus seperti model imbalance data untuk melihat performa tanpa perlu Teknik sampling guna melihat seberapa dan kenapa opini publik bereaksi terhadap suatu kebijakan pemerintahan khususnya terhadap anak anak sebagai output utama Kata Kunci: Pembatasan, Sentimen, Opini, Anak Anak, Media Sosial